Leadership style of administrators and professionalism of teachers in los banos district, division of laguna : an assessment - Bella, Artemio (Manila : National University, 1997)
School administrators have been found to be most effective when they score high on the dimensions of initiating structure and consideration. The findings of the study are expected to identify the areas under these two dimensions where they are perceived to be performing on a high or a low level.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of tables -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.